1997
DOI: 10.1007/bf02467129
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition diagram and regime of heat treatment of double-phase titanium alloys

Abstract: A substantiated choice of an optimum regime of heat treatment of titanium alloys is possible only on the basis of a complex investigation of the regular features of the structural and phase transformations and their relation with the mechanical properties after annealing conducted for different times and in a wide temperature range. The present work concerns low-temperature transformations in double-phase titanium alloys and their effect on the processes of embrittlement in a temperature range of 300 -800~ wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The impressive range of literature on the subject is, however, concentrated mostly on annealing of singlephase metallic materials -including alloys containing hard nonshearable particles. Studies on annealing in common two-phase (with shearable or semi-shearable 2nd phase) alloys are less frequent [39][40][41][42][43]; while such studies in two-phase Zr alloys are rare [44,45]. This was the motivation behind the present study.…”
Section: Introductionmentioning
confidence: 97%
“…The impressive range of literature on the subject is, however, concentrated mostly on annealing of singlephase metallic materials -including alloys containing hard nonshearable particles. Studies on annealing in common two-phase (with shearable or semi-shearable 2nd phase) alloys are less frequent [39][40][41][42][43]; while such studies in two-phase Zr alloys are rare [44,45]. This was the motivation behind the present study.…”
Section: Introductionmentioning
confidence: 97%
“…The obtained data of X-ray diffraction studies reflect the ability of titanium alloys to form metastable phases as a result of the mechanical and thermal treatment [8]. According to the published data, the weld zone and the heat-affected zone in titanium alloys have a different number of characteristic sections that reflect different limiting heating temperatures and different cooling rates [9].…”
Section: X-ray Diffraction Study Datamentioning
confidence: 91%
“…This process can be step-like, and each stage is complex. Thus, formation of stable and metastable phases takes place at the first stage [8]: formation of a stable α-Ti phase and formation of a metastable β-Ti phase. At the second stage, the metastable phase β-Ti can breakdown into a number of metastable phases ω-Ti, α′′-Ti and α2-Ti [8,11].…”
Section: X-ray Diffraction Study Datamentioning
confidence: 99%
“…Heating of supersaturated solid solutions of alloy D16 in the lower part αareas, in the temperature range 100...180°С and exposure times to 10 h (artificial aging), where the processes of structural relaxation developed by the relaxation mechanism, led to the decomposition of nonequilibrium solid solutions. Such microregions do not have an interface with the matrix, but have a different etching [22,23], were observed long before the appearance of particles Θ(CuAl2)-phase and were preallocations (Θ / -phase), that is, microvolumes in which phase transformations took place (restructuring of the crystal lattice) preceding the separation of the secondary Θ(CuAl2)phase, and accompanied by the occurrence of maximum structural stresses as a result of size mismatch at the interface "pre-release of the emerging Θ(CuAl2)-phase − α-matrix". α-solid solutions decay goes through the stages of microbundling, the formation of coherent predispositions (Θ / ) and isolation of particles of a new Θphase.…”
Section: New Materials and Technologies In Mechanical Engineeringmentioning
confidence: 99%
“…α-solid solutions decay goes through the stages of microbundling, the formation of coherent predispositions (Θ / ) and isolation of particles of a new Θphase. In the works [22][23][24][25] it is shown that a decrease in the relative elongation and contraction took place at the stage of completion of the microbinding of solid solutions and the formation of microblasts enriched in those impurity atoms that prevailed in the newly formed phase.…”
Section: New Materials and Technologies In Mechanical Engineeringmentioning
confidence: 99%